Impacts, vulnerability and adaptation to climate change in Brazil: an integrated approach - Marengo, José Antônio; Rodrigues-Filho, Saulo; Santos, Diogo Victor (Sustainability in Debate, 2021)
Impacts, vulnerability and adaptation to climate change in Brazil: an integrated approach